2015
DOI: 10.1091/mbc.e14-05-1020
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Tyro3 receptor and its intracellular partner Fyn signaling in Schwann cell myelination

Abstract: Schwann cells—peripheral myelin-forming glial cells—wrap around individual neurons. Tyro3 tyrosine kinase is a Schwann cell receptor that regulates myelination. Furthermore, Tyro3 interacts with the Fyn nonreceptor tyrosine kinase to promote myelination, representing a new receptor-linked signaling mechanism that controls myelination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 47 publications
3
22
1
Order By: Relevance
“…In addition to the delay in the initiation of myelination in the absence of Tyro3, we have identified alterations in the thickness of myelin ensheathing axons in both the optic nerve and in the corpus callosum. These observations complement a recently published study in which Tyro3 deficiency was associated with a reduction in the thickness of myelin produced by Schwann cells (Miyamoto et al, ). In combination, these observations indicate that Tyro3 is important for the regulation of both CNS and PNS myelination.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to the delay in the initiation of myelination in the absence of Tyro3, we have identified alterations in the thickness of myelin ensheathing axons in both the optic nerve and in the corpus callosum. These observations complement a recently published study in which Tyro3 deficiency was associated with a reduction in the thickness of myelin produced by Schwann cells (Miyamoto et al, ). In combination, these observations indicate that Tyro3 is important for the regulation of both CNS and PNS myelination.…”
Section: Discussionsupporting
confidence: 91%
“…Tyro3 is widely expressed in the CNS, particularly in developing white matter tracts (Prieto et al, 2000), although its function in the CNS remains largely unknown. In contrast, in the peripheral nervous system, Tyro3 was recently reported to regulate myelin sheath thickness by Schwann cells (Miyamoto et al, 2015). All three TAM receptors are expressed on OPCs, but whereas Axl and Mertk are subsequently absent from the lineage, Tyro3 is highly upregulated on newly formed and mature myelinating oligodendrocytes (Binder et al, 2008;Cahoy et al, 2008;Nielsen et al, 2006) and Tyro3 expression is lost upon genetic ablation of oligodendrocytes (Golan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Gas6 stimulated a higher activation state of Tyro3 after 3 h in the optic nerve, as observed by increased p-Tyro3 protein levels. This observation is supported by a recent study in the peripheral nervous system that showed Tyro3 to be an important modulator of myelination by Schwann cells ( Miyamoto et al., 2015 ).…”
Section: Discussionsupporting
confidence: 69%
“…Remyelination by oligodendrocytes is regulated by both intrinsic mechanisms and extrinsic factors from cells surrounding oligodendrocytes (Miron et al, 2011;Boulanger and Messier, 2014;El Waly et al, 2014;Tanaka and Yoshida, 2014), in the same manner as myelination by Schwann cells (Yamauchi et al, 2012;Miyamoto et al, 2015). Astrocytes function as cellular mediators of myelination and remyelination of oligodendrocytes by releasing various factors (PDGF, FGF2, CNTF, LIF, extracellular matrix-related molecules, etc.)…”
mentioning
confidence: 99%